PENILAIAN TINGKAT KEBERSIHAN GIGI TIRUAN SEBAGIAN LEPASAN AKRILIK BERDASARKAN METODE PEMBERSIHAN SECARA PENYIKATAN DAN LAMA PEMAKAIAN - Liana Rahmayani; Pocut Aya Sofya (ODONTO : Dental Journal, 2016)
Background: Acrylic removable partial denture can be cleaned by brushing method, soaking, or a combination of both. The level of cleanliness of acrylic removable partial denture affected by frequency, the cleaning method, the duration of usage and dentist instructions. The main objective of this study is to determine the level of cleanliness of acrylic removable partial denture based on the brushing cleaning method and duration of usage. Method: The subject in this study were 32 people that wear acrylic removable partial denture in the residential complex of PT. Arun NGL with purposive sampling technique. This study’s scoring was based on Reddick et al studies to determine the level of cleanliness of acrylic removable partial denture.Result:The results of this study showed that the subjects which using the brushing cleaning method, were 53,1% in cleaned category, 31,3% of the subjects was dirty category, and 15,6% were very dirty category.Conclusion:The conclution of this study is the level of majority subjects whose cleaning their denture by using the brushing method included to clean category in duration of usage from 0-10 years.Keywords: Cleanliness, Acrylic Removable Partial Denture, Brushing Method, duration of usage